Proceedings of the 40th Annual ACM SIGPLAN-SIGACT Symposium on Principles of Programming Languages 2013
DOI: 10.1145/2429069.2429127
|View full text |Cite
|
Sign up to set email alerts
|

Sub-polyhedral scheduling using (unit-)two-variable-per-inequality polyhedra

Abstract: International audiencePolyhedral compilation has been successful in the design and implementation of complex loop nest optimizers and parallelizing compilers. The algorithmic complexity and scalability limitations remain one important weakness. We address it using sub-polyhedral under-aproximations of the systems of constraints resulting from affine scheduling problems. We propose a sub-polyhedral scheduling technique using (Unit-)Two-Variable-Per-Inequality or (U)TVPI Polyhedra. This technique relies on simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…However, it would yield a huge number of polyhedral statements to be scheduled and scanned, which is incompatible with the complexity handled by current polyhedral model tools. Upadrasta and Cohen have shown that the execution time of Pluto increases in a roughly n 5 complexity in the number of statements in the system. In consequence, Pluto would introduce a high time overhead, which is inadequate for a runtime usage.…”
Section: Fast and Flexible Code Generationmentioning
confidence: 99%
“…However, it would yield a huge number of polyhedral statements to be scheduled and scanned, which is incompatible with the complexity handled by current polyhedral model tools. Upadrasta and Cohen have shown that the execution time of Pluto increases in a roughly n 5 complexity in the number of statements in the system. In consequence, Pluto would introduce a high time overhead, which is inadequate for a runtime usage.…”
Section: Fast and Flexible Code Generationmentioning
confidence: 99%
“…Some atomic options can be used to achieve more fine-grained control, such as the control of code size, the application of user-directives. Upadrasta et al [43] proposed a sub-polyhedral scheduling algorithm, which is based on TVPI (Two Variables Per Inequality) polyhedra with form of constraints:…”
Section: Code Generationmentioning
confidence: 99%
“…Let Z(m, n) be the complexity of ILP using the Simplex algorithm with m constraints and n variables. Then, on a typical input, Z(m, n) = O((m+n)mn) on average 2 [26]. In our ILP, this amounts to a complexity of (|E|+|V|)|E||V|, or |E| 2 |V|, or |V| 5 , i.e.…”
Section: Secondmentioning
confidence: 99%
“…This equips Polly also to achieve scalability as scalefuse, but the optimizer currently suffers from the same limitation (as above) of constructing separate schedules for basic blocks. Upadrasta et al [26] have identified this problem and have proposed a sub-polyhedral technique using (Unit-)Two-Variable-Per-Inequality or (U)TVPI Polyhedra. Their technique is an under-approximation of a general polyhedron, and thus does not guarantee to find best solutions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation